Explaining Pre-Service Early Childhood Teachers’ Intention of Implementing Museum Visits: An Extension of the Theory of Planned Behavior - Wu, Di (SAGE open, 2024)
Museums are traditionally considered public service settings with educational functions and practical learning resources for students. Early childhood teachers’ intention to implement class visits to museums is still very low. This paper synthesizes the theory of planned behavior model (TPB) and core determinants of the technology acceptance model (TAM) to hypothesize an extended TPB model to explain preschool teachers’ perceptions and intentions to implement museum visits. The results revealed that early childhood teachers’ intention of implementing class visits to museums was significantly influenced by attitude, perceived usefulness, and perceived behavioral control. The implications of this study are provided.